Trauma Time: The Queer Temporalities of the Traumatized Mind. (March 2017) - Morrigan, Clementine
Abstract : Queer theories of anti-futurity are maddened and cripped by reinserting disability, trauma, and child abuse into analysis of queer time. The queer temporalities of the traumatized mind, including dissociation, amnesia, hypervigilance, and ongoing disorientation in time, are explored. Resisting the imperative of a cure, the queer time traveling of trauma is positioned as a means of queer and mad world-making, and as a commitment to justice.